IBM Penyusunan Laporan Keuangan BUMDesa - Ummu Kalsum; Edy Susanto; Muhammad Arsyad (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of this activity was to increase the knowledge and ability of BUMDesa administrators, especially in recording and preparing BUMDesa financial reports. The method was used is training on recording and preparing BUMDesa financial reports by using lecture, tutorial, discussion (brainstorming) and post-training / mentoring techniques. The results of the activities obtained are increased knowledge and understanding of the accounting system, starting from the input in the form of recording transactions to the output that is produced in the form of BUMDesa financial reports containing financial information that will be used by BUMDesa stakeholders.